Pembubaran Ormas Islam oleh Pemerintah; Studi Komparatif Undang-Undang Ormas dan Hukum Islam - Syahrul Mubarak; Azman Arsyad (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab dan Hukum, 2021)
The concept of mass organizations is discussed in the legal order in Indonesia. Ormas itself or community organization is an organization founded and formed by the community voluntarily based on common aspirations, desires, needs, interests, activities, and goals to participate in development in order to achieve the goals of the Republic of Indonesia based on Pancasila and the Constitution of the Republic of Indonesia. 1945. The mass organizations were then unilaterally disbanded by the government with reference to the Law on the dissolution of Social Organizations and Islamic Law concerning the dissolution of community organizations. The main problem of this paper is how the concept of Islamic mass organizations in the legal order in Indonesia, how the indications for the unilateral dissolution of mass organizations by the government and how to review positive law and Islamic law regarding mass organizations. Community organization is a forum formed by a group of people who have the same vision, mission, ideology, goals and have clear members. According to the author, in one of the main principles of fiqhiyyah which is very popular among Muslims, it says that "the leader's policy towards the people is related to the benefit" of this fiqh rule the author takes the understanding that the government dissolves the Indonesian Islamic Defenders Front Community Organization to protect the Unitary State of the Republic of Indonesia from the goal. The main goal is to make Indonesia a caliphate state. So it is clear that according to the author, the legal determination carried out by the government by dissolving the Islamic Defenders Front Community Organization does not conflict with Islamic Shari'ah because the government prioritizes its benefit in enacting this law, in order to mantain the integrity of the Unitary State of the Republic of Indonesia and the state ideology, namely, Pancasila which is considered final. in Indonesia. Indonesia's ideology of Pancasila became one of the main reasons the government dissolved the Islamic Defenders Front Community Organization. The establishment of a caliphate state which is glorified by this Community Organization is considered not in accordance with the Unitary State of the Republic of Indonesia whose ideology is Pancasila and highly respects diversity in the harmony of state life